ENSO and West Pacific Seasonality Driven by the South Asian Monsoon - P. J. Tuckman; Jane E. Smyth; Jingyuan Li; Nicholas J. Lutsko; John Marshall (Geophysical Research Letters)
Abstract The equatorial Pacific exhibits a clear seasonal cycle, with West Pacific SSTs being highest during boreal autumn and El Niño/Southern Oscillation (ENSO) events tending to peak during boreal winter. In this work, we use the concept of a monsoonal mode and idealized coupled simulations to show that the presence of a large land mass in the Northern Hemisphere can lead to these seasonal asymmetries. Specifically, warm air moving east from the Asian summer monsoon suppresses surface fluxes in the West Pacific, leading to increased temperature there during the following months. The warmth of the West Pacific in boreal autumn strengthens the Walker circulation and the zonal temperature gradient across the Pacific, leading to the growth of El Niño events during that season. In summary, the presence of the Asian monsoon north of the equator results in ENSO events preferentially growing during boreal autumn and peaking during boreal winter.